Fabrication of uniform Ag/TiO2 nanotube array structures with enhanced photoelectrochemical performance - Lai, Yuekun (2013)
In the current work, pulse current deposition has been used to prepare evenly distributed and uniformly sized Ag nanoparticles on a TiO2 nanotube array photoelectrode. The Ag particle size and loading were controlled by the pulse deposition time. The Ag/TiO2 nanotube arrays were characterized by SEM, TEM, XRD, XPS and UV-vis diffuse reflection absorption. The resulting electrode contained intimately coupled, three-dimensional Ag/TiO2 structures with greatly improved photocurrent generation and charge transfer compared to a two-dimensional random Ag particle layer deposited directly on top of the nanotube array by the regular photoinduction method. A model mechanism is proposed to illustrate the uniform Ag nanoparticle deposition via the new deposition technique developed in the current work that promotes the uniform distribution of the Ag particles whilst minimizing their deposition at tube entrances, thus effectively preventing the pores from becoming clogged.